KOMUNIKASI SEBAGAI UPAYA UNTUK MEMBANGUN KETAHANAN KELUARGA DALAM KAJIAN "TEORI NILAI ETIK" - Al Amin, M. Nur Kholis (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2018)
Family is the main foundation for character formation and the role of family members. In addition, the family also plays a major role in the patterns of interaction that exist in people’s lives.  However, the development and changes that occur in society can effect the pattern (role) of family life. Today, the development of science and technology is able to influence the shape of society’s life structure toward the “modern society”, one of the impact on family structure is the existance of madern family, which is characterized by the intensity of meetings among family members is increasingly “limit” due to the high level of activity outside the household, such as: children who are out of town school, husband and wife career, husband who works outside the city and see also. Moreover, because the development of communication, so this can be made as a means to build family resilience. Therefore, this article will try to examine communication systems as a significant element to build family resiliaence throught historical contex and sociological approaches, where the presentasion is by integrating, describing, and the analyzing social phenomena—modern family life patterns, changes and developments in technology, communication—using “nilai etik theory” through several rules of Islamic communication as the value of communicating in the family. So that, when viewed from “nilai etik theory” develop by Rahman, conclusions can be obtained, that there are several elements of a very close relationship to the principles of Islamic communication, development of family structure, and family resilience as a way to build a family that is a sakinah, mawaddan and rahmah.Dewasa ini, perkembangan ilmu pengetahuan dan teknologi mampu mempengaruhi bentuk struktur kehidupan masyarakat ke arah “masyarakat modern”, yang salah satu dampaknya berpengaruh terhadap struktur yang ditandai dengan terbatasnya tingkat intensitas pertemuan antar anggota keluarga karena tingginya aktivitas di luar rumah tangga, seperti; anak yang sekolah atau kuliah di luar kota, suami-istri yang berkarir, suami yang bekerja di luar kota, dan sebaliknya. Lebih lanjut, karena perkembangan alat komunikasi yang semakin maju, maka hal tersebut dapat  dijadikan sebagai salah satu sarana untuk membangun ketahanan keluarga. Oleh karena itu, artikel ini akan coba menelaah sistem komunikasi sebagai unsur yang signifikan untuk membangun ketahanan keluarga melalui pendekatan historis (historical contex) dan pendekatan sosiologis, di mana pemaparannya dengan cara memadukan, mendeskripsikan, dan kemudian menganalisis fenomena sosial—pola kehidupan keluarga modern, perubahan dan perkembangan teknologi, komunikasi—menggunakan teori nilai etik melalui beberapa kaidah komunikasi Islam sebagai nilai berkomunikasi di dalam keluarga. Sehingga, apabila ditinjau dari “teori nilai etik” yang dikembangkan oleh Rahman, dapat diperoleh kesimpulan, bahwa terdapat beberapa unsur hubungan yang sangat erat terhadap prinsip-prinsip komunikasi Islam, perkembangan struktur keluarga, dan ketahanan keluarga sebagai jalan untuk membangun keluarga yang sakinah, mawaddah dan rahmah.